STRATEGI PENGEMBANGAN USAHA TERNAK AYAM PEDAGING DI PROVINSI SULAWESI TENGAH - Rustam Abd Rauf; Rosida Adam (Agroland: Jurnal Ilmu-ilmu Pertanian, 2014)
The research aimed to identify and to analyze the need and inventory of broiler chicken, and to generate strategy for broiler farm business development in Central Sulawesi Province.  It was a descriptive (qualitative and quantitative) survey research in which the number of respondents was 552 people. The need of broilers for Central Sulawesi was found to be 3,804,225.68 kg month-1 in total or for one district 345,838.70 kg month-1 in average which was equal to 197,622.11 broilers.  The total shortage of broiler inventory for Central Sulawesi was 3,367,285.68 in totalor for one district 306,116.88 in average which was equal to 174,923.93 broilers month-1. The scores of IFAS and EFAS analyzed were 1.471 for strengths (S), 1.394 for weaknesses (W), 1.766 for opportunities (O) and 1.280 for threats (T). These scores suggest that the development of broiler chicken in Central Sulawesi is positioned on SO strategy. The strategic issues and activities recommended to be implemented for developing the broiler chicken farmingincluding (1) increasing production through extending chicken shed area, (2) improving farmers’ knowledge, (3) establishing and developing partnership between farmers and entre preneursso that it can dominate the market and the availability of local feed.